Edukasi Penggunaan Bengkung yang Aman dan Tepat pada Ibu Nifas sebagai Upaya Mendukung Pemulihan Pascapersalinan - Kristina Maharani (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The postpartum period is a critical phase in which mothers experience physiological and psychological recovery. Bengkung, a traditional abdominal binding cloth, is commonly used by Indonesian postpartum mothers, but inappropriate application may cause discomfort and may not support recovery optimally. This community service program aimed to improve postpartum mothers' knowledge and skills regarding safe and appropriate bengkung use. The activity was conducted through counseling, demonstration, guided practice, and evaluation using a one-group pre-test and post-test approach involving 30 postpartum mothers at a community-based maternal health service setting. The educational content covered postpartum physiological changes, indications and contraindications, safe binding principles, hygiene, duration of use, warning signs, and when to seek professional care. The evaluation showed an increase in good knowledge from 26.7% before education to 86.7% after education, and correct practice skills increased from 20.0% to 83.3%. Participants also reported better understanding of avoiding overly tight binding, maintaining breathing comfort, and discontinuing use when pain, shortness of breath, excessive bleeding, or wound problems occur. This activity indicates that structured education and demonstration can strengthen postpartum self-care and support safer integration of traditional practices into maternal health services.